2011
DOI: 10.1088/0957-4484/22/7/075302
|View full text |Cite
|
Sign up to set email alerts
|

Imprinting nanoporous alumina patterns into the magneto-transport of oxide superconductors

Abstract: We used oxygen ion irradiation to transfer the nanoscale pattern of a porous alumina mask into high-T(C) superconducting thin films. This causes a nanoscale spatial modulation of superconductivity and strongly affects the magneto-transport below T(C), which shows a series of periodic oscillations reminiscent of the Little-Parks effect in superconducting wire networks. This irradiation technique could be extended to other oxide materials in order to induce ordered nanoscale phase segregation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Irradiation with O + ions (energy E = 110 keV) through the mask induces disorder in the YBCO film, in particular oxygen vacancies and interstitials. Note that contrary to masked ion milling techniques [52], here the material is not etched and the sample surface is not affected [53] by the ion irradiation: only point defects are created in the bulk of the material. These defects are strongly concentrated in the regions directly exposed to the ion beam through the mask holes.…”
Section: Methodsmentioning
confidence: 99%
“…Irradiation with O + ions (energy E = 110 keV) through the mask induces disorder in the YBCO film, in particular oxygen vacancies and interstitials. Note that contrary to masked ion milling techniques [52], here the material is not etched and the sample surface is not affected [53] by the ion irradiation: only point defects are created in the bulk of the material. These defects are strongly concentrated in the regions directly exposed to the ion beam through the mask holes.…”
Section: Methodsmentioning
confidence: 99%
“…by the amplitude of the field matching effects observed in the magnetotransport-is generally found to be much weaker in high-T C (e.g. YBa 2 Cu 3 O 7-δ ) 18,21,22 than in low-T C superconductors (e.g. Nb) 1 .…”
mentioning
confidence: 99%
“…Therefore the ions are fully stopped by the mask and reach the YBCO film only through the mask holes. O + ion bombardment does not change the YBCO surface morphology 21 , but creates point defects within the bulk of the material 21 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, pinning effects by ordered arrays of defects have been intensively studied in both conventional low temperature superconductors [17][18][19][20][21][22] and high temperature superconductors [23][24][25][26][27] for several decades. Recently, YBCO films that contained periodic vortex pinning arrays created via masked ion irradiation demonstrated strong matching-field effects verifying the prevalence of periodic pinning over intrinsic random pinning [23,28]. Also, guided vortex motion in YBCO film with asymmetric artificial defects created by FIB patterning, recently confirmed that higher pinning forces than those from intrinsic defects, could be achieved by precise artificial pinning potential designs [24].…”
Section: Introductionmentioning
confidence: 87%